Spinal Involvement of TRPV1 and PI3K/AKT/mTOR Pathway During Chronic Postoperative Pain in Mice - Gabriela Xavier Santos; Tayllon dos Anjos-Garcia; Ana Carolina de Jesus Vieira; Giovane Galdino (Brain Sciences)
Background: Chronic postoperative pain (CPOP) is among the main consequences of surgical procedures, directly affecting the quality of life. Although many strategies have been used to treat this symptom, they are often ineffective. Thus, studies investigating CPOP-associated mechanisms may help to develop more effective treatment strategies. Therefore, the present study investigated the spinal participation of the transient potential receptor vanilloid type 1 (TRPV1) and PI3K/AKT/mTOR pathway activation during CPOP. Methods: In this study C57BL/6 male mice were used, and CPOP was induced by muscle retraction and incision. The nociceptive threshold was measured by the von Frey filament test. For pharmacological evaluation, TRPV1 and PI3K/AKT/mTOR inhibitors were administered intrathecally. TRPV1 and PI3K/AKT/mTOR protein levels were evaluated by Western blotting. Results: The results showed that CPOP increased TRPV1 and mTOR protein levels, and pretreatment with the specific inhibitors alleviated CPOP. In addition, pretreatment with the TRPV1 antagonist SB-366791 attenuated mTOR protein levels. Conclusions: The results suggest that TRPV1 and the PI3K/AKT/mTOR pathway are involved in CPOP at the spinal level, and TRPV1 may activate mTOR during this process.